Determination of the Critical Micelle Concentration of Neutral and Ionic Surfactants with Fluorometry, Conductometry, and Surface Tension—A Method Comparison - Scholz, Norman; Behnke, Thomas; Resch-Genger, Ute (Journal of fluorescence, 2018)
Micelles are of increasing importance as versatile carriers for hydrophobic substances and nanoprobes for a wide range of pharmaceutical, diagnostic, medical, and therapeutic applications. A key parameter indicating the formation and stability of micelles is the critical micelle concentration (CMC). In this respect, we determined the CMC of common anionic, cationic, and non-ionic surfactants fluorometrically using different fluorescent probes and fluorescence parameters for signal detection and compared the results with conductometric and surface tension measurements. Based upon these results, requirements, advantages, and pitfalls of each method are discussed. Our study underlines the versatility of fluorometric methods that do not impose specific requirements on surfactants and are especially suited for the quantification of very low CMC values. Conductivity and surface tension measurements yield smaller uncertainties particularly for high CMC values, yet are more time- and substance consuming and not suitable for every surfactant.